2011
DOI: 10.1371/journal.pone.0019864
|View full text |Cite
|
Sign up to set email alerts
|

T Cells from Programmed Death-1 Deficient Mice Respond Poorly to Mycobacterium tuberculosis Infection

Abstract: BackgroundProgrammed Death-1 (PD-1; CD279) receptor molecule is widely believed to be a negative regulator predominantly expressed by exhausted/activated mouse T cells. Upon interaction with its ligands, PD-L1 and PD-L2, PD-1 inhibits activation of T cells and cytokine production, which has been documented in various viral and fungal infections as well as in vitro studies. Therefore, inhibition of T cell responses by PD-1 resulted in disease resistance in a variety of mouse infection models studied heretofore.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 47 publications
2
71
2
4
Order By: Relevance
“…PD-1 is a B7-family protein expressed on exhausted T cells and is responsible for loss of effective control in chronic infection and cancer (38). In contrast, mice lacking PD-1 are more susceptible to M. tuberculosis infection (39)(40)(41). KLRG1 expression is a surrogate marker of terminally differentiated, short-lived effector CD8 T cells in inflammation and viral infection models (42).…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 is a B7-family protein expressed on exhausted T cells and is responsible for loss of effective control in chronic infection and cancer (38). In contrast, mice lacking PD-1 are more susceptible to M. tuberculosis infection (39)(40)(41). KLRG1 expression is a surrogate marker of terminally differentiated, short-lived effector CD8 T cells in inflammation and viral infection models (42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, infection of PD-1 KO mice with BCG leads to enhanced T-cell responses and bacterial control rather than immunopathology (Sakai et al 2010). However, rather than displaying enhanced protection, PD-1 knockout mice succumb rapidly on exposure to low doses of virulent Mtb (Lázár-Molnár et al 2010;Barber et al 2011;Tousif et al 2011). It was found that PD-1 KO mice have greatly increased numbers of I-A b ESAT-6 1 -20 tetramer-binding CD4 T cells in their lungs and that transient depletion of CD4 T cells in the first month of infection prevented the severe tissue destruction and death of the PD-1 KO mice .…”
Section: Negative Regulation Of T-cell Responses During Tuberculosismentioning
confidence: 99%
“…Curiously, recent studies showed that PD-1 −/− mice exhibited an altered response to infection with mycobacteria, characterized by uncontrolled bacterial burden; massive production of cytokines, termed "cytokine storm"; and early death (23)(24)(25). We wondered if this unique response of PD-1 −/− mice to mycobacteria contributed to their Th response in EAE.…”
mentioning
confidence: 99%